Using logarithmic fuzzy preference programming to prioritization social media utilization based on tourists' perspective - Mina Balouchi; Ehsan Khanmohammadi (Foundations of Management, 2015)
The advent of Web 2.0 or social media technologies gives travelers a chance to access quickly and conveniently to a mass of travel-related information. This study investigates the importance of social media in travel process in three different phases (pre-visit, on site, post-visit) from the perspective of Iranian travelers. It is worthwhile to know the level of influence of social media on respondents' travel behavior. Logarithmic fuzzy preference programming methodology is used in this article to determine the importance of social media usage in each phase of travel process and its subcategories. Fuzzy analytic hierarchy process methodology, based on Chang's Fuzzy Extent Analysis is also used for the data analysis, then the results of these two methods are presented for comparison and better understanding. The results of this study suggest that the most usage of social media is on pre-visit phase while post-visit has the least usage. This study shows that Iranian travelers use social media mainly to share experiences (post-visit phase), get help in different circumstances and gain travel advice.
Keywords: 650; social media; LFPP; travel process; user generated content; tourism marketing